The age of enlightenment in melanoma immunotherapy. Issue 1 (22nd August 2018) - Albertini, Mark R.
Abstract : An updated survival analysis by Callahan et al. published in the February 1, 2018 issue of the Journal of Clinical Oncology reported a 3-year overall survival (OS) rate of 63% for 94 patients with previously treated or untreated advanced melanoma who received ipilimumab and nivolumab as concurrent therapy in a phase 1 dose escalation study CA209–004 ( n  = 53) or in an expansion cohort with the dose and schedule of concurrent ipilimumab and nivolumab now approved for patients with unresectable or metastatic melanoma ( n  = 41). While this 3-year OS rate of 63% in patients with measurable, unresectable stage III or IV melanoma is an impressive accomplishment that compares very favorably with historical metastatic melanoma survival rates, findings from larger phase 3 studies are needed to determine whether combination immunotherapy significantly improves survival more than single agent immunotherapy with PD-1 blockade. This Commentary discusses the transition from the dark ages to the age of enlightenment in melanoma immunotherapy and provides a roadmap for a better tomorrow for patients with metastatic melanoma.